Minimal and Maximal Beta Open Sets - Shakir, Qays Rashid (Al-Nahrain Journal of Science, 2018)
The present paper deals and discusses new types of sets all of these concepts completely depended on the concept of Beta open set. The importance concepts which introduced in this paper are minimal -open and maximal -open sets. Besides, new types of topological spaces introduced which called and spaces. Also we present new two maps of continuity which called minimal -continuous and maximal -continuous. Additionally we investigated some fundamental properties of the concepts which presented in this paper.